Could an El Niño event put dietary supplies of n‐3 long‐chain polyunsaturated fatty acids (EPA and DHA) in jeopardy - Pike, Ian H.; Tocher, Douglas R. (European Journal of Lipid Science and Technology, 2016)
The beneficial effects of n‐3 long‐chain polyunsaturated fatty acids, especially EPA and DHA, for human health are widely recognised. Intakes of these fatty acids in many parts of Europe fall far short of the recommended intake, especially in young people. The most robust evidence from human health studies demonstrating beneficial effects is that for cardiovascular disease. Other beneficial effects have been reported for inflammatory diseases such as rheumatoid arthritis, Crohn's disease and ulcerative colitis, cognitive and visual development in pre‐term infants and on various psychological/behavioural and psychiatric disorders. For European consumers fish is the main source of EPA and DHA, especially oily fish, and in particular farmed Atlantic salmon. With evidence of a strong El Niño type event occurring in the Pacific currently (2015/16), fish stock biomasses have drastically declined and permitted fishing heavily reduced. Subsequent fish oil shortages have resulted in increased substitution of fish oil with vegetable oil in feeds for farmed salmon. A significant fall in EPA and DHA in these fish and a reduction in intake by consumers are expected in the short term. Avoiding fish oil shortages causing reductions in EPA and DHA intake by consumers in the future may be possible through the production of DHA‐rich algal biomass if the cost can be reduced. Genetically modified crops which might also be a source of these fatty acids are unlikely to be acceptable for salmon feeds in Europe in the near future. Practical applications: If farmed Atlantic salmon is to continue to be an important source of EPA and DHA in European diets, especially those in the UK, consideration will have to be given to obtaining new sources of these fatty acids. It would be prudent to follow the development of cheaper forms of DHA‐rich algal biomass for incorporation into salmon feeds. Any relaxation of the public's objections to the use of genetically modified crops to produce ingredients for salmon feeds should be followed. It may ...